2014
DOI: 10.1039/c3cp54398f
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected effects of the alteration of structure and stability of myoglobin and hemoglobin in ammonium-based ionic liquids

Abstract: The nature of solvent-biomolecule interactions is generally weak and non-specific. The addition of ionic liquids (ILs), which have emerged as a new class of solvents, strengthen the stability of some proteins whereas the same ILs weaken the stability of some other proteins. Although ILs are commonly used for the stabilization of biomolecules, the bimolecular interactions of their stabilization-destabilization is still an active subject of considerable interest and studies on this topic have been limited. To re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 75 publications
3
104
0
1
Order By: Relevance
“…This leads to strong exclusion of less hydrated TEAP from the water molecules at the surface of protein in comparison to TMAP.So far literature considered anion effect on protein stability91 recently, we for the first time showed the effect of cation chain length on the structural stability of well known heme proteins Hb and Mb 92. We observed unfolding of heme protein induced by cations.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…This leads to strong exclusion of less hydrated TEAP from the water molecules at the surface of protein in comparison to TMAP.So far literature considered anion effect on protein stability91 recently, we for the first time showed the effect of cation chain length on the structural stability of well known heme proteins Hb and Mb 92. We observed unfolding of heme protein induced by cations.…”
mentioning
confidence: 74%
“…Conversely, Jha et al 92 bring into being that the thermal stability of the heme proteins Mb and Hb decreased with decrease in alkyl chain of the cation. Thus, the short alkyl chain cation containing IL TMAH was more denaturing than more hydrophobic long chain cation TBAH.…”
Section: Effect Of Alkyl Chain Length Of Cation Of Ammonium-based Il mentioning
confidence: 94%
“…The decreased stability of BSA in the presence of ILs is attributed to the interactions of the hydrophobic group of IL with the hydrophobic region in the cavity of BSA. Interactions between functional groups of BSA and ions of IL and repulsive intermolecular interaction between functional groups of BSA cannot be ignored in the process of unfolding/ decreased T m values of BSA . These interactions loosen the native structure which leads to disruption of tertiary structure evidenced by the CD spectra discussed later in this section.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent survey, it is found that the aqueous solution of ILs improves the stability, activity, and refolding ability of the protein by suppressing their irreversible aggregation . However, they also have some adverse effects on proteins i. e. destabilize the proteins/enzymes …”
Section: Introductionmentioning
confidence: 99%